Actual y futura disponibilidad del agua en un contexto de inseguridad hídrica en la subcuenca de Parón, cuenca del río Santa, Perú - Izaguirre Liviac, Marcos Fabio; Drenkhan, Fabian; Timaná, Martín (Pontificia Universidad Católica del Perú, 2024)
Water security in Andean watersheds depends on adaptive water management in the face of glaciohydrological and socioeconomic impacts. The Parón sub-basin in the Santa River basin (Ancash, Peru) is a suitable case in this respect. Water is regulated by a floodgate in the Parón lake, which has become a focal point of social conflict. This study analyzes the water balance of this sub-basin using a semi-distributed hydrological model for the present (2006-2016) and future (2030-2050), considering different scenarios of precipitation variation, glacial melting, and increased water demand. Without regulation of the lake, the sub-basin would enter into a strong water deficit in the dry months (June-August). Until 2030 (2050), assuming a maximum regulation of 2.6 m³/s, a 15% (35%) increase in precipitation, and a 10% (26%) decrease in the glacier contribution to the annual flow, water availability would be reduced by 37% (35%). In a pessimistic scenario with a 15% (35%) decrease in precipitation, water availability would still be reduced by 47% (56%) annually. These results highlight the need to keep a socially acceptable minimum water flow (>2 m³/s) to avoid critical levels of water scarcity in the dry months and to address the needs of local water users.

La seguridad hídrica en las cuencas andinas depende de una gestión adaptativa del agua ante los impactos glaciohidrológicos y socioeconómicos. La subcuenca Parón en la cuenca del río Santa (Áncash, Perú) representa un caso idóneo en este aspecto. El agua es regulada mediante una compuerta en la laguna Parón, convertida en un punto focal de conflicto social. Este estudio analiza el balance hídrico de esta subcuenca mediante un modelo hidrológico semidistribuido para el presente (2006-2016) y futuro (2030-2050), considerando diferentes escenarios de variación de la precipitación, derretimiento glaciar e incremento de la demanda del agua. Sin regulación de la laguna, la subcuenca entraría en un fuerte déficit hídrico en los meses de estiaje (junio-agosto). Hasta el 2030 (2050), asumiendo una regulación máxima de 2.6 m³/s, un aumento de la precipitación en 15% (35%) y una disminución de la contribución glaciar al caudal en 10% (26%) a nivel anual, la disponibilidad hídrica se reduciría en 37% (35%). En un escenario pesimista con una disminución de la precipitación en 15% (35%), la disponibilidad hídrica se reduciría aún en 47% (56%) anualmente. Estos resultados resaltan la necesidad de mantener un mínimo de caudal de agua (>2 m³/s) socialmente aceptable para evitar niveles críticos de escasez hídrica en los meses de estiaje y para satisfacer las necesidades de los usuarios de agua locales.
Current and future water availability in the context of water insecurity in the Parón catchment, Santa River basin, Peru
Keywords: Glacier retreat; Future scenarios; Water balance; Water security; Cordillera Blanca; Hydrological model; Peru; Retroceso glaciar; Escenarios futuros; Balance hídrico; Seguridad hídrica; Cordillera blanca; Modelo hidrológico; Perú; https://purl.org/pe-repo/ocde/ford#2.07.01